Ultrasonic Parameters as Biomarkers for Tumor Staging and Aggressiveness in Breast Cancer: Correlation with GP73 and miR-27a - Tao ZY; Rong R; Zhou LP (International Journal of General Medicine)
Zi-Yu Tao,1,* Rong Rong,2,* Lei-Ping Zhou3 1Obstetrics and Gynecology Hospital Fudan University, Shanghai, 200233, People’s Republic of China; 2Department of Clinical Laboratory, The Second People’s Hospital of Hefei, Hefei Hospital Affiliated to Anhui Medical University, Hefei, 230000, People’s Republic of China; 3Department of Ultrasound, International Peace Maternity and Child Health Hospital, Shaghai, 200063, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lei-Ping Zhou, Department of Ultrasound, International Peace Maternity and Child Health Hospital, Shaghai, 200063, People’s Republic of China, Tel +86-13761708810, Email Zhouleiping68@163.comObjective: To investigate correlations between CEUS parameters and serum GP73/miR-27a in breast cancer.Methods: In the study, 117 highly suspected breast cancer diagnosed and treated in our hospital during March 2022 to April 2024 were included. Meanwhile, pathologic examination was used as the gold standard for diagnosis in this study. The 117 subjects were divided into breast cancer group (69 cases) and non-breast cancer group (48 cases). Both groups underwent contrast-enhanced ultrasound (CEUS), and the parameters of peak intensity (PI), time to peak (TTP), wash-inslope (WIS), gradient (Grad) were recorded. The levels of GP73 and miR-27 in serum of both groups were examined. The relationship between ultrasonography parameters and serum GP73 and miR-27a expression levels was evaluated by correlation analysis.Results: CEUS parameters (PI, WIS, Grad) in cancer patients were significantly higher than benign group (P< 0.05), while TTP was lower. GP73 and miR-27a levels were elevated in cancer patients (P< 0.05), with stage III–IV showing higher values than stage I–II (P< 0.05). GP73 correlated positively with Grad (r=0.330, P=0.006), while miR-27a correlated with WIS (r=0.311, P=0.009) and Grad (r=0.424, P< 0.001). ROC analysis revealed AUCs of 0.771– 0.776 for individual parameters and 0.945 for combined markers.Conclusion: CEUS parameters and serum GP73/miR-27a levels correlate with breast cancer severity, demonstrating synergistic diagnostic value (AUC=0.945), supporting their combined use for early detection and progression assessment.Keywords: breast cancer, ultrasonic parameters, GP73, miR-27a, correlation analysis